Examining English Language Instructors’ Practice of Reflective Teaching Components in Ethiopia - Nigatu Habtamu; Badima Belay (Educational Challenges)
Reflective teaching, which has attracted attention globally as an integral component of teacher pedagogy, is still a difficult concept to understand. Probably, because it is attainable only when the practitioners are committed to practice it, seeing it as the best opportunity for their professional development through critical thinking about their teaching.